2020
DOI: 10.32598/irj.18.4.1016.2
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acceptance and Commitment Therapy on the Sense of Coherence, Locus of Control, and Posttraumatic Growth in Patients With Multiple Sclerosis

Abstract: Objectives: This study aimed to determine the effects of Acceptance and Commitment Therapy (ACT) on the Sense of Coherence (SOC), Locus of Control (LoC), and Posttraumatic Growth (PTG) in patients with Multiple Sclerosis (MS). These factors were explored according to the prevalence of psychological problems in these patients. Methods: This was a quasi-experimental study with a pre-test, post-test and a control group design. The study population included all patients with MS from Iran’s MS Association in Tehran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…SoC-comprising the patients capacity to understand the situation, and find meaning and means to move in a health promoting direction, that is, comprehensibility, meaningfulness, and manageability-presents a stress-coping resource (10,39,40), which has been shown to beneficially impact quality of life and mental outcome upon transplantation (11,41). We promote reciprocal benefit of the two major health concepts of self-efficacy and SoC, particularly in the pretransplant situation of patients evaluated for HTx and therefore propose complementation of resource-oriented interventions with SoC-oriented therapy, as, for example, acceptance and commitment therapy, which has been shown to be beneficial in other contexts (42,43). Several studies have supported the use of a general psychosocial exploration protocol before wait-listing (35), and important aspects must be assessed before organ transplantation wait-listing, for example, to predict posttransplant medication adherence (44).…”
Section: Discussionmentioning
confidence: 99%
“…SoC-comprising the patients capacity to understand the situation, and find meaning and means to move in a health promoting direction, that is, comprehensibility, meaningfulness, and manageability-presents a stress-coping resource (10,39,40), which has been shown to beneficially impact quality of life and mental outcome upon transplantation (11,41). We promote reciprocal benefit of the two major health concepts of self-efficacy and SoC, particularly in the pretransplant situation of patients evaluated for HTx and therefore propose complementation of resource-oriented interventions with SoC-oriented therapy, as, for example, acceptance and commitment therapy, which has been shown to be beneficial in other contexts (42,43). Several studies have supported the use of a general psychosocial exploration protocol before wait-listing (35), and important aspects must be assessed before organ transplantation wait-listing, for example, to predict posttransplant medication adherence (44).…”
Section: Discussionmentioning
confidence: 99%
“…The main difference between post-traumatic growth and resilience is that while resilience permits the person to survive and adapt to the adverse situation without significant difficulties, in post-traumatic growth, a stress-induced positive change leads the person to function better than before the traumatic experience. Thus, it has been demonstrated that MS patients with a higher level of resilience experience less post-traumatic growth ( Younesi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Post-traumatic growth has been widely explored in various medical conditions, for example, acquired brain damage ( Rogan et al, 2013 ), cardiac outpatient ( Leung et al, 2010 ), myocardial infarction ( Rahimi et al, 2016 ; Hosseini Golafshani et al, 2021 ), cancer ( Heidarzadeh et al, 2014 ), and liver transplantation ( Pérez-San-Gregorio et al, 2017a ). There is evidence that most MS patients undergo some degree of post-traumatic growth ( Aflakseir and Manafi, 2018 ; Younesi et al, 2020 ), even though the underlying mechanisms are poorly understood. Pakenham and Cox (2009) discovered a significant connection between duration of MS and personal growth, but only in patients who had been diagnosed over 15 years before.…”
Section: Introductionmentioning
confidence: 99%